„Civilis, non tyrannica dominatio” (Tert. Apol. 2.14.) : Miért nem álltak ellen a keresztények a római hatalom üldözéseinek? - Grüll, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
In the first three centuries of the existence of Christianity, it was exposed to sporadic and then increasingly organized persecution by the authorities of the Roman Empire. All of the Christian apologists emphasized the illegality of these persecutions. Tertullian, the jurist, who worked under Septimius Severus, emphasized that the Roman Empire is a state of law, not a tyrannical rule, and this law did not allow the execution of innocents. Although the number of Christians continued to grow despite the persecutions – in Carthage, for example, at the end of the 3rd century, one in ten inhabitants of the city declared themselves to be Christians – it seems that they resigned themselves to the constant oppression. In the Apologeticum, Tertullian lists three possible forms of resistance: internal disruption, open armed rebellion, or mass emigration, but he considers them both unjust and impracticable. According to him, the persecutions were approved by God in order to purify his Church. At the same time, there is also an eschatological reason why they did not stand against the tyrannical oppression: some Christian theologians interpreted the statement in 2 Thessalonians 2:7 about the “one who now holds it back” (niv) or “he who now restrains it” (esv), viz. who prevents the appearance of the Antichrist as being the Roman Empire or the emperor itself. If the current emperor falls, the Empire itself will collapse, and the “ten kings” will come, who will be the direct forerunners of the Antichrist. This is why Christians honour the emperors and they do not oppose them by force even if they are sent to death by the imperial authorities.